2022
DOI: 10.1038/s41598-022-22089-0
|View full text |Cite
|
Sign up to set email alerts
|

Broadband infrared study of pressure-tunable Fano resonance and metallization transition in 2H-$$\hbox {MoTe}_2$$

Abstract: High pressure is a proven effective tool for modulating inter-layer interactions in semiconducting transition metal dichalcogenides, which leads to significant band structure changes. Here, we present an extended infrared study of the pressure-induced semiconductor-to-metal transition in 2H-$$\hbox {MoTe}_2$$ MoTe 2 , which reveals that the metallization process at 13–15 GPa is not associated with the indirect band-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…It is worth noticing that a similar analysis conducted on Mo 0.5 W 0.5 S 2 gave a metallization threshold very close to the average P M FIR of MoS 2 and WS 2 , which is exactly what would be expected for an alloy compound. Moreover, a good correspondence between the metallization onset obtained from pressure-dependent FIR measurements and pressure-dependent transport measurements was found for MoTe 2 . These results obtained on three different TMD semiconductors and a TMD alloy indicate the SW analysis of the FIR spectrum as a reliable approach for the detection of the metallic behavior in this class of materials.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…It is worth noticing that a similar analysis conducted on Mo 0.5 W 0.5 S 2 gave a metallization threshold very close to the average P M FIR of MoS 2 and WS 2 , which is exactly what would be expected for an alloy compound. Moreover, a good correspondence between the metallization onset obtained from pressure-dependent FIR measurements and pressure-dependent transport measurements was found for MoTe 2 . These results obtained on three different TMD semiconductors and a TMD alloy indicate the SW analysis of the FIR spectrum as a reliable approach for the detection of the metallic behavior in this class of materials.…”
supporting
confidence: 61%
“…In bulk MoTe 2 , resistivity measurements found evidence of the onset of a metallic behavior at P M res ∼ 10−12 GPa, 16,18 while the effective closure of the band gap was observed at ∼24 GPa through absorption measurements in the near-infrared (NIR). 19 In a similar vein, resistivity 20 and impedance 21 measurements carried out on bulk MoS 2 suggested the crystal becomes metallic at P M res ∼ 20 GPa, while absorption measurements in the NIR/visible range showed that the band gap closes at pressures higher than 26 GPa. 22 As for the other semiconductors belonging to the class of TMDs, like WS 2 , in the majority of cases, the definition of the metallization threshold only relies on transport measurements, 23 while there lacks a direct estimate of the pressure-dependent trend of the band gap.…”
mentioning
confidence: 88%
See 3 more Smart Citations